Genome-wide identification of foxtail millet’s TRX family and a functional analysis of SiNRX1 in response to drought and salt stresses in transgenic Arabidopsis - Zhang, Shuangxing; Yu, Yang; Song, Tianqi; Zhang, Mingfei; Li, Nan; Yu, Ming; Zhou, Hongwei; Yang, Yanning; Guo, Sihai; Xu, Chunhong; Tu, Yongle; Xiang, Jishan; et al. (Frontiers in Plant Science, 2022)
Thioredoxins (TRXs) are small-molecule proteins with redox activity that play an important role in the growth, development, and stress resistance of plants. Foxtail millet (Setaria italica) gradually became a model crop for stress resistance research because of its advantages such as its resistance to sterility and its small genome. To date, the thioredoxin (TRX) family has been identified in Arabidopsis thaliana, rice and wheat. However, studies of the TRX family in foxtail millet have not been reported, and the biological function of this family remains unclear. In this study, 35 SiTRX genes were identified in the whole genome of foxtail millet through bioinformatic analysis. According to phylogenetic analysis, 35 TRXs can be divided into many types. The chromosome distribution, gene structure, cis-elements and conserved protein motifs of 35 SiTRXs were characterized. Three nucleoredoxin (NRX) members were further identified by a structural analysis of TRX family members. The expression patterns of foxtail millet's SiNRX members under abiotic stresses showed that SiNRXs have different stress-response patterns. In addition, subcellular localization revealed that SiNRXs were localized to the nucleus and plasma membrane. Further studies showed that the overexpression of SiNRX1 enhanced Arabidopsis' tolerance to drought and salt stresses; the overexpressing lines showed a higher survival rate and better growth performance. In addition, the expression levels of several known stress-related genes were generally higher in overexpressed lines than in the wild-type. This study identified the genome-wide structural characteristics of 35 TRX family members of millet, and a further analysis showed that SiNRX1 enhanced the drought and salt resistance of transgenic Arabidopsis. These results provide a general picture of the TRX family in foxtail millet and lay a foundation for further research on the mechanism of the action of TRX proteins on abiotic stresses.